A review on aeromoniasis in poultry: A bacterial disease of zoonotic nature - Wafaa A Abd El-Ghany (Journal of Infection in Developing Countries)
Aeromonas spp. are widely distributed in surface water, sewage, untreated and chlorinated, drinking water, as well as meats, fish, shellfish, poultry, and their products. A disease caused by Aeromonas spp. is designated as aeromoniasis. It can affect different aquatic animals, mammals, and birds in different geographic regions. Moreover, gastrointestinal and extra-intestinal disease conditions may be provoked in humans as a result of food poising with Aeromonas spp. Some Aeromonas spp. have been identified, however, Aeromonas hydrophila (A. hydrophila), A. caviae, and A. veronii bv sobria may be of public health significance. Aeromonas spp. are members of family Aeromonadaceae and genus Aeromonas. They are Gram-negative rod-shaped, facultative anaerobic, and oxidase and catalase-positive bacteria. The pathogenicity of Aeromonas in different hosts is mediated by several virulence factors such as endotoxins, cytotoxic enterotoxin, cytotoxins, hemolysins, adhesins, and extracellular enzymes such as proteases, amylases, lipases, ADP-ribosyltransferases, and DNases. Most avian species are susceptible to either natural or experimental infections with Aeromonas spp. Infection usually arises through feacal-oral route. Traveler’s diarrhea as well as other systemic and local infections are the clinical picture of food poisoning associated with aeromoniasis in humans. Despite Aeromonas spp. being sensitive to various antimicrobials, multiple drug resistance has been commonly reported worldwide. Accordingly, this review highlights aeromoniasis in poultry regarding Aeromonas virulence factors epidemiology, pathogenicity, zoonosis, and antimicrobial resistance.